The bounds-test approach for co-integration between international tourist arrivals, per capita income and cost of living: the case of All Cyprus - Yorucu, Vedat; Mehmet, Ozay (Routledge Journals, Taylor & Francis Ltd, 2011)
Tourism is a major income earner for Cyprus, but the market is a divided destination. Since 1974 the country has been divided into the North and the South, each competing with one another in the same tourism market. For the first time, this empirical study investigates an island-wide tourism demand. Extending earlier work (Yorucu, 2001), All Cyprus tourism time series data covering 1980-2006 has been used in this article to estimate demand applying standard bounds-test approach for co-integration within a disaggregated framework. The results confirm a special long-run equilibrium relationship between Turkey/North Cyprus and Greece/South Cyprus. Thus, per capita tourist arrivals from Greece to South Cyprus and those from Turkey to North Cyprus are statistically significant with cost of living and per capita income variables. So long as incomes per capita increase in Turkey and Greece, a reunited All Cyprus will gain as one destination as Turkish and Greek citizens will become mobile island-wide.
Keywords: Time-Series; Growth